Performance optimization of a simulation study on phase change material for photovoltaic therm - Noordin Saleem, Siti Nur Dini; Mohd Rosli, Mohd Afzanizam; Sanusi, Nortazi; Salimen, Nurfarhana; Herawan, Safarudin Gazali; Abdullah, Qaharuddin (Penerbit Akademia Baru, 2022)
The integration of Phase Change Material (PCM) with the Solar Photovoltaic Thermal (PVT) serves as heat storage to enhance the system's performance. Temperature rises have an undesirable effect on efficiency results in a diminishment in the amount of energy produced by the solar panel. Parametric analysis and temperature investigation are involved in improving the performance of the system. The variation of performance will assist in developing an optimized PVT-PCM system. The model is validated by comparison from published journals on the studies related to phase change material implemented in solar PVT. For the variation of mass flow rate, the overall efficiencies achieved by 10 kg/h, 30 kg/h, 50 kg/h and 70 kg/h are 90.82%, 90.54%, 90.48% and 90.46%, respectively. In addition, solar irradiance of 200 W/m2, 450 W/m2 and 800 W/m2 produced 91.17%, 90.82% and 90.33% of overall efficiencies. Increased in flow rate requires stronger pumps which increase the total cost of the system. Therefore, identifying the optimal flow rate might help to achieve an appropriate thermal efficiency while sustaining in low costs. Finally, this paper presented a numerical investigation of PCM acts as promising elements incorporated in the PVT system that has the capability to reduce the temperature of the PVT-PCM system.